(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Current transport mechanism in thin films of complex of Zr(IV) with Cyclodichlorophosphazene trimer (PNCl2)3 have been studied under normal and different illuminating conditions. It is found that at low field the film exhibits ohmic behaviour and the high field region is dominated by Richardson-Schottky (RS) mechanism. Keywords : Cyclodichlorophosphazene trimer; Richardson-Schottky; Ohmic behaviour DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8190 Bangladesh J. Sci. Ind. Res. 46(2), 231-234, 2011